Impact of multidisciplinary team care in breast cancer treatment planning - Safna Naozer Virji; Syeda Alisha Fatima Rizvi; Lubna Mushtaque Vohra; Abida Khalil Sattar; Sana Zeeshan (Journal of the Pakistan Medical Association, 2026)
Globally, breast cancer remains the most prevalent cancer among women, with multidisciplinary team care emerging as the gold standard for its management. The multidisciplinary team care integrates expertise from diverse specialists, including oncologists, radiologists, pathologists and nurses, to develop individualised, evidence-based treatment plans. This collaborative approach improves diagnostic accuracy, enhances patient outcomes, and fosters holistic care by addressing both medical and psychosocial needs. Studies show that multidisciplinary team involvement leads to better survival rates, reduced treatment variability, and improved quality of life. However, challenges, such as resource limitations, logistical barriers and communication inefficiencies, can hinder its effectiveness, particularly in low-resource settings. Advances in telemedicine and virtual multidisciplinary teams are improving access and streamlining collaboration, especially in underserved areas. To optimise multidisciplinary team care, ongoing training, patient-centred decision-making and technological integration are essential. Multidisciplinary team care ensures comprehensive breast cancer treatment, enhances patient satisfaction, and sets the foundation for continued improvements in cancer management. Keywords: Breast cancer, Multidisciplinary treatment, Patient-centered care, Quality of life.